Association of maternal characteristics with induced vaginal deliveries and its outcome: a hospital-based study in Karnali Academy of Health Sciences, Nepal - Basnyat, Subi; Khapung, Robin; Baral, Gehanath; Silwal, Shirish; Basnyat, Nikita; Panta, Prem Prasad; Magar, Sadikshya Budha; Khadka, Nisha (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Induction of labor (IOL) is commonly practiced obstetric intervention aimed at initiating uterine contractions before spontaneous labor onset when continuation of pregnancy may pose maternal or fetal risks. Its outcomes vary by indication, maternal characteristics, cervical favorability, and resource availability. Limited data exist on IOL outcomes from remote regions of Nepal. The main objective of our study was to evaluate the indications, methods, and outcomes of IOL at Karnali Academy of Health Sciences (KAHS), Jumla, and to determine associations between gestational age, maternal characteristics, and labor outcomes.Method: A retrospective observational study was conducted among all singleton, cephalic pregnancies ≥34 weeks undergoing IOL from January to December 2024. Data were extracted from labor registers and analyzed using SPSS 16. Descriptive statistics summarized demographic and clinical variables. Chi-square tests assessed associations between induction and gestational age, maternal age, and parity.Result: Among 800 deliveries, 122 (15.3%) underwent induction. Most common indications were post-term pregnancy (28.8%) and late-term pregnancy (21.9%). Significant association was found between gestational age and method of labor onset (p < 0.001). Parity showed significant association when grouped into nulliparous vs multiparous (p = 0.0037). Maternal complications were low, with first- and second-degree perineal tears being most common. Postpartum hemorrhage occurred in only 0.48% of induced cases.Conclusion: IOL practices at KAHS follow global guidelines and show good maternal outcomes. Induction was mainly for evidence-based reasons and linked to low maternal complications. Standardized protocols, better documentation, and ongoing labor monitoring could further improve outcomes in remote areas.